Peran Suami dalam Kesenjangan Berumah Tangga (Studi Kasus Pernikahan Teuku Ryan dan Ria Ricis) - Laila Rahmi Hasanah; Syifa Sofhia; Baihaki Fatur Rahman; Dwi Noviani (STIKes Ibnu Sina Ajibarang, 2024)
Marriage is an agreement between two people, generally, a man and a woman, to live together to achieve happiness. It is not only about two people but also about families, achieving happiness is not easy if both families have different backgrounds, values , and views on life to build a relationship together to form a large family from a marriage. Conflict often occurs due to external factors from the surrounding environment, including the family, such as the gap between in-laws and in-laws. This research aims to find out the roles of husbands, wives, and in-laws in responding to the gap between wives and biological mothers in the case study of Teuku Ryan and Ria Ricis's marriage. The analysis technique for this research uses a literature review. The research results show that all aspects play an important role in maintaining family harmony, so if one aspect has a gap, then the risks that can occur include disputes and even divorce. Therefore, it is necessary to communicate and approach each other to avoid existing risks.